Inverse theorems on approximation of periodic functions - Stepanets, O. I. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We obtain new inverse theorems on the approximation of periodic functions f(·) that establish conditions for the existence of their (ψ, β)-derivatives. These theorems also guarantee a certain smoothness of these derivatives.